Multiple functions of Drosophila heat shock transcription factor in vivo. - Jedlicka, P.; Mortin, M.A.; Wu, C. (The EMBO Journal, 1997)
Heat shock transcription factor (HSF) is a transcriptional activator of heat shock protein (hsp) genes in eukaryotes. In order to elucidate the physiological functions of HSF in Drosophila, we have isolated lethal mutations in the hsf gene. Using a conditional allele, we show that HSF has an essential role in the ability of the organism to survive extreme heat stress. In contrast to previous results obtained with yeast HSF, the Drosophila protein is dispensable for general cell growth or viability. However, it is required under normal growth conditions for oogenesis and early larval development. These two developmental functions of Drosophila HSF are genetically separable and appear not to be mediated through the induction of HSPs, implicating a novel action of HSF that may be unrelated to its characteristic function as a stress-responsive transcriptional activator.